Low Temperature Conductivity in n-Type Noncompensated Silicon below Insulator-Metal Transition - A. L. Danilyuk; A. G. Trafimenko; A. K. Fedotov; I. A. Svito; S. L. Prischepa (Advances in Condensed Matter Physics)
We investigate the transport properties of n-type noncompensated silicon below the insulator-metal transition by measuring the electrical and magnetoresistances as a function of temperature T for the interval 2–300 K. Experimental data are analyzed taking into account possible simple activation and hopping mechanisms of the conductivity in the presence of two impurity bands, the upper and lower Hubbard bands (UHB and LHB, resp.). We demonstrate that the charge transport develops with decreasing temperature from the band edge activation (110–300 K) to the simple activation with much less energy associated with the activation motion in the UHB (28–90 K). Then, the Mott-type variable range hopping (VRH) with spin dependent hops occurs (5–20 K). Finally, the VRH in the presence of the hard gap (HG) between LHB and UHB (2–4 K) takes place. We propose the empiric expression for the low T density of states which involves both the UHB and LHB and takes into account the crossover from the HG regime to the Mott-type VRH with increasing temperature. This allows us to fit the low T experimental data with high accuracy.